تأمين بيئة العمل للمنشآت البحثية والتعليمية وعلاقة ذلك بالرضا الوظيفي للباحثين العاملين بهذه المنشآت - إبراهيم، سحر حسن; عجرمة، فاطمة عبدالمحيي (الجمعية الأكاديمية المصرية للتنمية البيئية, 2015)
بالرغم من التطور الهائل في أساليب العمل الفني والتكنولوجي، إلا أن القوى العاملة ستظل ركيزة التنمية ومحركها الأساسي. وحيث أن المراقب لواقع تأمين بيئة العمل في المنشآت ذات الصلة بالبحث والتعليم الفني والتكنولوجي يلاحظ افتقارها لكثير من قواعد السلامة والصحة المهنية وتأمين بيئة العمل، مع ما قد يسببه ذلك من تزايد احتمالات إصابات العمل والأمراض المهنية؛ ورغم أن الاهتمام بالسلامة والصحة المهنية وتأمين بيئة العمل يعد ضرورة من ضروريات التنمية وتحسين الإنتاج لما له من آثار اجتماعية واقتصادية، إلا أنه أصبح استجابة ضرورية لمتطلبات معايير الجودة والاعتماد لهذه المنشآت؛ ولهذا يهدف البحث الراهن إلى الكشف عن العلاقة بين تأمين بيئة العمل للمنشآت البحثية والتعليمية وعلاقتها بالرضا الوظيفي للباحثين العاملين في هذه المنشآت. ولتحقيق هدف الدراسة تم تطبيق استبانتين إحداهما لاختبار الرضا الوظيفي، والأخرى لقياس تطبيق معايير السلامة والصحة المهنية وتأمين بيئة العمل، على مجموعة من الباحثين العاملين في بعض المراكز البحثية والتعليمية، لمعرفة آرائهم حول مدى تطبيق معايير السلامة والصحة المهنية وتأمين بيئة العمل، وارتباط ذلك برضاهم عن العمل داخل هذه المنشآت. وقد أشارت نتائج الدراسة إلى وجود علاقة دالة بين تأمين بيئة العمل، وتقييم مخاطر الحريق، والرضا الوظيفي ببعديه الرضا عن نوع العمل، والرضا عن علاقات العمل. بينما لم تكن هناك علاقة دالة بين تأمين بيئة العمل وتقييم مخاطر الحريق والرضا عن نظام العمل. في حين كانت هناك علاقة دالة بين تقييم المخاطر السلبية والرضا الوظيفي بأبعاده الثلاث (الرضا عن نوع العمل، والرضا عن نظام العمل، والرضا عن علاقات العمل). Despite the tremendous development in the technical and technological methods of work, yet the workforce will still the pillar of development and its basic engine. The observer of the reality of securing environmental work in the research and technical education and technological installations can notice lack of many occupational safety and health and secure work environment rules, which may cause increasing likelihood of work injuries and occupational diseases. Also, despite the fact that interest in occupational safety and health and secure work environment is necessary for development and improvement of production because of its social and economic impact, but it has become a necessary response to the requirements of quality and certification standards for these facilities. So this research aims to detect the relationship between secure work environment for research and educational facilities and job satisfaction of employees to carry out researchers at these facilities. To achieve the objective of this study, two questionnaires were applied, one to test the job satisfaction and the other to measure the application of occupational safety and health and labor insurance environment standards, on a group of researchers working in some research and educational centers to learn their views on the extent of the application of occupational health and safety and secure work environment standards, and link it to their job satisfaction within these facilities. The study results indicated the presence of significant relationship between secure work environment, assessment of the risk of fire and job satisfaction, with its two dimensions, satisfaction with the type of work, and satisfaction with job relations. On the other hand, there were no relationships between secure work environment and assessment of the risk of fire and satisfaction of job system. However, there was a significant correlation between the negative risk assessment and job satisfaction and their three dimensions (satisfaction of the job type, satisfaction of job system, and satisfaction of the labor relations).
Keywords: التعليم الفني -- الصحة المهنية -- منظمة الصحة العالمية -- الأمراض الوبائية